2016
DOI: 10.1371/journal.pone.0166498
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF-Producing Th Cells in Rats Sensitive and Resistant to Experimental Autoimmune Encephalomyelitis

Abstract: Given that granulocyte macrophage colony-stimulating factor (GM-CSF) is identified as the key factor to endow auto-reactive Th cells with the potential to induce neuroinflammation in experimental autoimmune encephalomyelitis (EAE) models, the frequency and phenotype of GM-CSF-producing (GM-CSF+) Th cells in draining lymph nodes (dLNs) and spinal cord (SC) of Albino Oxford (AO) and Dark Agouti (DA) rats immunized for EAE were examined. The generation of neuroantigen-specific GM-CSF+ Th lymphocytes was impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 61 publications
(128 reference statements)
7
11
0
Order By: Relevance
“…We could not detect IL‐27 in the supernatant of DLN cells stimulated with PLP 139‐151 from relapsing‐EAE SJL mice and IL‐27 blockade had no effect on MOG 35‐55 EAE C57BL/6 mice, so we did not investigate this further (data not shown). Lastly, the comparative analysis of EAE‐sensitive and EAE‐resistant rat strains revealed that GM‐CSF + cells were decreased in DLNs from EAE‐resistant rat strain, with the majority of these cells being IL‐17 − IFNγ − , demonstrating that production of GM‐CSF and IL‐17 and IFNγ are not always co‐expressed . Altogether, these results provide evidence for a phenotypic heterogeneity in cells producing IL‐17, IFNγ and GM‐CSF, thereby supporting the specific effect we observed of anti‐GM‐CSF treatment on IL‐17 production independently from IFNγ.…”
Section: Discussionsupporting
confidence: 72%
“…We could not detect IL‐27 in the supernatant of DLN cells stimulated with PLP 139‐151 from relapsing‐EAE SJL mice and IL‐27 blockade had no effect on MOG 35‐55 EAE C57BL/6 mice, so we did not investigate this further (data not shown). Lastly, the comparative analysis of EAE‐sensitive and EAE‐resistant rat strains revealed that GM‐CSF + cells were decreased in DLNs from EAE‐resistant rat strain, with the majority of these cells being IL‐17 − IFNγ − , demonstrating that production of GM‐CSF and IL‐17 and IFNγ are not always co‐expressed . Altogether, these results provide evidence for a phenotypic heterogeneity in cells producing IL‐17, IFNγ and GM‐CSF, thereby supporting the specific effect we observed of anti‐GM‐CSF treatment on IL‐17 production independently from IFNγ.…”
Section: Discussionsupporting
confidence: 72%
“…This implies that they are more efficient in antigen-presentation and activation of T cells. This assumption is in accordance with earlier data from our group and others that draining lymph node cellularity increases faster and to the greater extent in DA rats in response to encephalitogenic immunization [13,20]. Similar results were observed in the contact hypersensitivity reaction [21].…”
Section: Have the Central Role In The Activation Of Naïve T Cells supporting
confidence: 93%
“…Higher IL-10 release from AO rat DC is also in accordance with our previous report on the increased IL-10 expression and production in AO rat lymph nodes and within the CNS of the immunized rats [17]. Interestingly, IL-6 generation is also higher in AO rat DC, while the clear dominance of DA rat lymph node cells in production of IL-6 was observed in previous reports [14,20]. Since there are multiple cellular sources of IL-6 within unseparated population of lymph node cells, cell-specific regulation of IL-6 production in relation to the strain specificity is worthy of further studies.…”
Section: Have the Central Role In The Activation Of Naïve T Cells supporting
confidence: 92%
“…Rats of both strains were randomly assigned to immunization (“immunized for EAE” group) or left untreated (“non-immunized” group). For induction of EAE, rats received 100 μl of an emulsion made of equal volumes of rat spinal cord (SC) homogenate in phosphate-buffered saline (PBS) and complete Freund’s adjuvant (CFA) containing 1 mg/ml of heat-killed and dried Mycobacterium tuberculosis H37Ra (Sigma-Aldrich Chemie GmbH, Taufkirchen, Germany) into the left hind foot pad, and 0.25 ml of saline suspension of 5 × 10 8 Bordetella pertussis (Institute of Virology, Vaccines and Sera “Torlak“, Belgrade, Serbia) subcutaneously into the dorsum of the same paw [ 42 ]. To diminish stress, pain and injury, rats were administered an intraperitoneal injection of ketamine (Ketamidor, Richter Pharma AG, Wels, Austria; 100 mg/ml)/xylazine (Xylased, Bioveta, Ivanovice na Hané, Czech Republic; 20 mg/ml) anesthetizing cocktail [50 mg/kg body weight (BW) of ketamine/5 mg/kg BW xylazine].…”
Section: Methodsmentioning
confidence: 99%
“…Having all the aforementioned in mind, female Dark Agouti (DA) rats (susceptible to EAE induction) and Albino Oxford (AO) rats (relatively resistant to EAE induction) [ 42 ] were examined for the influence of immunization for EAE on: i) quantitative and qualitative characteristics of thymopoiesis (generation of distinct subpopulation of conventional T cells and CD4+ nTregs), and ii) the phenotypic profile of the main subpopulations of T-peripheral blood lymphocytes (T-PBLs) in terms of the frequency of RTEs, as an indicator of thymopoietic efficacy [ 43 ], and CD28- T cells, as their accumulation, which could also be associated with thymic atrophy, contributes to target tissue damage [ 44 ]. Additionally, to elucidate the putative mechanisms underlying thymopoietic changes, thymic tissue was examined for the expression of molecules regulating thymocyte precursor cell entry into the thymus (CXCL12) [ 45 ], their survival and differentiation/maturation (IL-7, IL-6) [ 46 49 ], and differentiation/maturation of CD4+ nTregs (IL-2, IL-15) [ 50 ].…”
Section: Introductionmentioning
confidence: 99%